Perception Analysis of Industrialized Building System (IBS) Implementation for G7 Contractors in Kuching, Sarawak - Abdullah, N.M.Q.B.; Lee, Y.Y.; Lee, Yeong Huei; Gui, H.C.; Whyte, Andrew (2021)
Industrialized Building System (IBS) is one of the initiatives underpinning the green construction zeitgeist. A myriad of advantages can be associated with adopting IBS in construction, including inter alia, improved construction quality and productivity, minimisation of construction waste, optimisation of construction materials on-site, enhanced environmental sustainability, and many others. In spite of these advantageous propositions, there is exist a gap in the exposure towards IBS construction methods, particularly in the city of Kuching, Sarawak, as compared to more familiar conventional methods. Thus, the purpose of this study is to identify the issues and challenges experienced by contractors in their IBS endeavour as well as to propose a framework of solution. Moreover, this study investigated the impact of IBS adoption by G7 contractors registered with the Construction Industry Development Board (CIDB) of Sarawak. Data of this study was collected via questionnaires distributed to the G7 contractors and subsequently analysed using descriptive and mean analysis. Results obtained from the study suggested that IBS construction method enhances the efficiency of construction for speedier completions, which recorded the highest ranking. Conversely, lowering the costs of construction through optimisation of materials registered the lowest ranking, suggesting that contractors do not necessarily perceive IBS as having a cost-saving ability. This study showed that IBS helps to improve the efficiency of the construction process. However, respondents were still uncertain that adopting IBS can reduce costs. This corresponds to the finding in which the most significant challenge perceived by the contractors was related to cost. This suggested a lack of integration between the different stakeholders, especially during the design stage, often resulting in the need for redesign works that required additional costs when IBS is to be adopted. In this regard, it was not a surprise to find that “promotions” obtained the top ranking as a solution in overcoming the IBS challenges. Hence, support from both the government and the private sector needs to be garnered and diligently promoted, so that the adoption of IBS in the Sarawak construction industry can be properly enhanced.